Compliance with the Use of Fe Tablets by Pregnant Women in Preventing and Handling Anemia - N. Sulami; D. Mariza; U. Hasanah; O. Ramadani (Sean Institute, 2026)
Compliance with iron consumption significantly impacts the health of pregnant women and their fetuses. Anemia is a major public health problem worldwide, especially for women of reproductive age. For pregnant women, anemia contributes to an increased prevalence of maternal mortality and morbidity, and for infants, it can increase the risk of infant morbidity and mortality, as well as Low Birth Weight (LBW). The contribution of anemia to maternal and infant mortality is estimated to be even higher, between 50-70%. This figure can be reduced if pregnant women receive a daily intake of 90 iron tablets and supplementation with vitamin B12 and folic acid. The causes of anemia in pregnant women are iron deficiency caused by a lack of iron-containing food sources, adequate food sources with low iron content resulting in insufficient iron absorption, and foods consumed containing substances that inhibit iron absorption. This study aimed to determine the compliance of pregnant women in consuming iron tablets. This was a quantitative descriptive study, with all pregnant women at the Rasana'e Timur Community Health Center (Puskesmas) participating. Data analysis used a frequency distribution table.